Durasi Pengobatan Berpengaruh terhadap Jumlah Tiap Jenis Leukosit Penderita Tuberkulosis Paru - Karol Octrisdey; Made Susilawati; Fitri Rachmillah Fadmi; Winioliski L. O. Rohi Bire (Holistic Nursing and Health Science, 2026)
Pulmonary tuberculosis (TB) remains one of the major public health challenges in Indonesia. The immune response to TB infection may be influenced by the treatment duration, which can be observed through changes in the composition of leukocyte types in patients undergoing therapy. However, limited studies identify the duration of TB treatment with leukocyte type count among pulmonary TB patients. This study aimed to analyze the influence of the treatment duration on leukocyte type count in pulmonary TB patients. This study implied an analytical observational design and involved 60 pulmonary TB patients selected from several health facilities. Data were collected through laboratory examinations to assess leukocyte profiles and medical record reviews to determine the treatment phase based on the duration of therapy. The data were analyzed univariately to describe the respondents’ characteristics by age and sex, and bivariate analysis used simple linear regression to assess the relationship between treatment phase and changes in leukocyte proportions. Findings showed significant effects of the treatment duration on the proportions of eosinophils (p = 0.032), lymphocytes (p = 0.005), and neutrophils (p = 0.018). Patients in a longer treatment phase exhibited an increase in lymphocyte counts, while eosinophils and neutrophils tended to decrease. These results indicate that the immune response to TB adjusts over time and that leukocyte profiles may serve as indicators of treatment effectiveness. This study provides valuable insights for healthcare professionals in understanding the immune dynamics of TB patients and optimizing therapeutic strategies to enhance treatment outcomes. AbstrakTuberkulosis paru masih menjadi tantangan besar kesehatan masyarakat di Indonesia. Respon imun terhadap infeksi tuberkulosis paru dapat mengalami perubahan sesuai dengan lama pengobatan, yang tercermin melalui perbedaan proporsi jenis leukosit pada pasien yang menjalani terapi. Penelitian yang mengindentifikasi pengaruh lama terapi tuberkulosis terhadap jumlah tiap jenis leukosit penderita tuberkulosis paru masih terbatas. Penelitian ini bertujuan untuk mengetahui pengaruh lama pengobatan terhadap tiap jenis leukosit (eosinofil, limfosit, monosit, dan neutrofil) pada pasien tuberkulosis paru. Desain penelitian ini adalah observasional analitik dengan jumlah sampel 60 pasien dari berbagai fasilitas layanan kesehatan. Data dikumpulkan melalui pemeriksaan darah dan penelaahan rekam medis untuk menentukan lama pengobatan. Analisis univariat digunakan untuk menggambarkan karakteristik responden, sedangkan uji regresi linear digunakan untuk mengevaluasi hubungan antara lama pengobatan dan komposisi jenis leukosit. Hasil menunjukkan adanya pengaruh yang signifikan antara lama pengobatan dengan jumlah eosinofil (p = 0,032), limfosit (p = 0,005), dan neutrofil (p = 0,018). Semakin lama pengobatan dijalani, terjadi peningkatan limfosit serta penurunan eosinofil dan neutrofil. Temuan ini menunjukkan adanya adaptasi imun selama terapi tuberkulosis paru dan dapat menjadi dasar dalam memantau efektivitas pengobatan.